A Survey on Autonomous Vehicles-Benefits and Drawbacks - Sushma, R.; Kumar, J. Satheesh (Journal of Electronics and Informatics, 2023)
Making roads safer is a subject that has received a lot of attention recently in the media, public policy circles, and in general health and wellness talks. A startling proportion of the incidents are avoidable, and many of them are caused by distracted driving. A stronger effort has been made in the field of technology in recent years to make automobiles safer, drivers more attentive, and accidents less likely as a consequence of the amount of traffic accidents that plague the nation and the tragic injuries and fatalities that come from them. Self-driving vehicles are a development that seems to fit in a sci-fi movie, along with other technology that has evolved during this period. Self-driving cars are not that far off, but the argument over whether they will boost or diminish safety continues to rage. In the not-too-distant future, self-driving cars stand a great chance of taking over as the primary mode of transportation. The use of self-driving automobiles has a lot of benefits, but there are some disadvantages as well. This essay explains the benefits and drawbacks of self-driving automobiles.